Unique cellular immune signatures of multisystem inflammatory syndrome in children. - Anuradha Rajamanickam; Pavan Kumar Nathella; Aishwarya Venkataraman; Poovazhagi Varadarjan; Srinithi Kannan; Arul Nancy Pandiarajan; Rachel Mariam Renji; Elayarani Elavarasan; Akshith Thimmaiah; Kandasamy Sasidaran; Nedunchelian Krishnamoorthy; Suresh Natarajan; et al. (PLoS Pathogens)
The clinical presentation of MIS-C overlaps with other infectious/non-infectious diseases such as acute COVID-19, Kawasaki disease, acute dengue, enteric fever, and systemic lupus erythematosus. We examined the ex-vivo cellular parameters with the aim of distinguishing MIS-C from other syndromes with overlapping clinical presentations. MIS-C children differed from children with non-MIS-C conditions by having increased numbers of naïve CD8+ T cells, naïve, immature and atypical memory B cells and diminished numbers of transitional memory, stem cell memory, central and effector memory CD4+ and CD8+ T cells, classical, activated memory B and plasma cells and monocyte (intermediate and non-classical) and dendritic cell (plasmacytoid and myeloid) subsets. All of the above alterations were significantly reversed at 6-9 months post-recovery in MIS-C. Thus, MIS-C is characterized by a distinct cellular signature that distinguishes it from other syndromes with overlapping clinical presentations. Trial Registration: ClinicalTrials.gov clinicaltrial.gov. No: NCT04844242.